The skinny rules : the simple, nonnegotiable principles for getting to thin - Harper, Bob (Ballantine Books, 2012)
Bob Harper, superstar trainer and co-host of NBC's hit show "The Biggest Lose," distills his vast knowledge of nutrition, weight-loss strategy, and human nature down to twenty simple, nonnegotiable principles and offers a month's worth of menu plans and more than 90 delicious, rule-abiding recipes for breakfast, lunch, dinner, and snacks to keep you cooking and eating skinny for life.